Advancing Indonesia's UMKM: From Survival to Scalable Innovation - Setiawan, Agus (Innovation, Technology, and Entrepreneurship Journal, 2026)
This editorial argues that Indonesia's UMKM sector conflates digitalization with advancement. Payment infrastructure has scaled fast: QRIS now covers most merchants nationwide and processes billions of transactions a year. Financial capability, market competence, operational maturity, and technology adoption stay uneven across the ecosystem. The editorial reviews 2026 conditions, where macro growth stays positive while individual businesses face tighter margins and more selective consumer spending. It proposes four capability pillars, financial and data discipline, market competence, operational maturity, and technology as an accelerator, and closes with a direct research agenda and practical guidance for UMKM owners.